Redefining Molecular Chaperones as Chaotropes - Macošek, Jakub; Mas, Guillaume; Hiller, Sebastian (Frontiers in Molecular Biosciences, 2021)
Molecular chaperones are the key instruments of protein homeostasis; they facilitate folding of clients, transport them, prevent their aggregation, dissolve aggregates or unfold misfolded proteins. Despite this seemingly large variety, multiple of these functions can be performed by a single chaperone and with low client specificity, suggesting a single common mechanism underlying. In line with this notion, unfolding of client proteins emerges as a common feature crucial to functions of most chaperones. Several recently elucidated structures of bacterial chaperone–client complexes have revealed that dynamic interactions stabilize conformationally flexible non-native states, which results in client unfolding. Based on the emerging understanding of chaperone function in solution and its similarity to chaotropic agents, we propose chaperone chaotropicity to constitute the generic unfoldase activity that is central to chaperone function.